Integration of the Computer Games into Early Childhood Education Pre-Service Teachers' Mathematics Teaching - Tokmak, Hatice Sancar; Incikabi, Lutfi (IGI Global, 2013)
Mathematics experiences in the early years of education can help children be more prepared for the future. Mathematics is known to be one of the most difficult learning areas. Computer games in today's technological world seem to offer a way to educate young children in mathematics in a fun and engaging way. However, success does not rely solely on the technology itself, but also how it is used during instruction. For that reason, early childhood teachers have a responsibility to integrate technology into their instruction, and to understand such technologies with regard to content and audience. Therefore, this chapter provides an example of how to incorporate educational computer games into upper-level education courses. The instructor designed the course described in this chapter to teach early childhood teachers how to integrate educational computer games for the purpose of teaching mathematics to young children.
Keywords: 4. Education